The club convergence of efficiency in ASEAN banking sector - Awang Marikan, Dayang Affizah; Abdul Rahim, Rossazana; Habibullah, Muzafar Shah; Rahman, Md. Mahbubur (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
The study examines the internal financial structure of ASEAN banking and its efficiency. In doing so, it concentrates on the characteristics of banking sector efficiency and practises within the ASEAN countries banking sectors by using Phillips and Sul (2007a, 2007b and 2007c) approach. Firstly, by applying non-parametric Data Envelopment Analysis (Simar and Wilson, 2007) technique, it considers the technical efficiency of ASEAN banks. The outcome confirms that, at the aggregate level, the ASEAN banking markets are diverging. Further investigation indicates comparatively weak convergence between banking sector of ASEAN though there is still potential of catching up process between them. It can be concluded that ASEAN countries are inter-related and most of the banks are catching up within the different club and different degree of convergence. In terms of efficiency, the results show that at aggregate level, the ASEAN countries are competitive among each other acknowledged by the identification of 3 convergence clubs. The study is able to gain an insight overview regarding ASEAN banking efficiency and its ability to catch up between member countries. These could lead to a successful financial integration, fullfiling the objective to create a potential single currency within ASEAN countries in the near future.